Anatomic resection versus radiofrequency ablation with an ablative margin ≥ 1.0 cm for solitary small hepatocellular carcinoma measuring ≤ 3 cm: Comparison of long-term outcomes using propensity score matching analysis. Issue 155 (October 2022) - Zhang, Chunchen; Gao, Ruize; Guo, Shigang; Ning, Chunmin; Li, Aolei; Wang, Xiangtao; Li, Shangsheng; Ding, Jianhua; Kong, Xinliang; Wang, Qiang; Xu, Yanjie; Li, Jiaqi; et al.
Abstract: Purpose: To compare the long-term outcomes of anatomic resection (AR) and radiofrequency ablation (RFA) with an ablative margin (AM) of ≥ 1.0 cm as first-line treatment for solitary hepatocellular carcinoma measuring ≤ 3 cm. Methods: Two hundred and fifty-one patients who underwent AR (n = 156) or RFA (ablative margin ≥ 1.0 cm, n = 95) at any of 6 tertiary hospitals from 2009 to 2018 were enrolled. Propensity score matched analysis (PSM) were used to compare overall survival (OS), recurrence-free survival (RFS), and perioperative outcomes. Univariate and multivariate analyses were performed to identify prognostic factors associated with RFS and OS. Results: PSM created 67 patient-pairs. After 96 months of follow-up, RFA with an ablative margin ≥ 1.0 cm and AR showed comparable 1-year, 3-year, 5-year, and 8-year OS rates before ( P  = 0.580) and after ( P  = 0.640) PSM. However, RFS was better at 1, 3, 5, and 8 years after AR before ( P  = 0.0036) and after ( P  = 0.017) PSM. The operation time and postoperative hospital stay were significantly longer in the AR group than in the RFA group before and after PSM ( P  < 0.05). Multivariate analysis identified age and type of treatment to be independent prognostic factors for RFS and age and hepatitis C to be associated with OS. Conclusions: Long-term OS was not significantly different between AR and RFA with an AM ≥ 1.0 cm in patients with a solitary hepatocellular carcinoma measuring ≤ 3 cm; but, RFS appeared to be better after AR than after RFA. However, RFA was associated with fewer perioperative complications and a shorter postoperative hospital stay.